The effects of procrastination on physical activity among Chinese university students: the chain-mediated effects of time management disposition and exercise motivation - Zhang, Yuan; Tian, Maoshen; Yang, Jian; Xi, Yue; Li, Zhihui; Wang, Lin (Frontiers in Psychology, 2024)
Objectives Grounded in self-determination theory (SDT), the procrastination-health model, and the mechanism model of exercise persistence, this study examined the effects of procrastination on physical activity and the mechanism of its action in Chinese college students. Design This study employed a cross-sectional design. Methods A total of 957 Chinese university students (Mage = 20.26, SD = 1.07) completed questionnaires. The Aitken Procrastination Questionnaire, the Adolescent Time Management Dispositions Scale (ATMDS), the Modified Physical Activity Motivation Measure-Revised (MPAM-R), and the Physical Activity Rating Scale (PARS-3) were used to measure procrastination, time management disposition, exercise motivation, and physical activity. Results Procrastination, time management disposition, exercise motivation, and physical activity were each significantly correlated, and procrastination was a significant negative predictor of physical activity. The mediating effect of time management disposition and exercise motivation in the effect of procrastination on physical activity was significant, and the mediating effect accounted for 44.65% of the total effect. Three paths were specifically included: first, the separate mediating effect of time management disposition, second, the separate mediating effect of exercise motivation, and third, the chain mediating effect of time management disposition and exercise motivation. Conclusion This study reveals the mechanism of action by which procrastination influences physical activities through time management disposition and exercise motivation in Chinese college students. The findings provide guiding recommendations for further promoting greater participation in physical activities among college students.